Forecast Audit towards 2016 Gross Domestic Product as Influence of Financial Growth and the ASEAN Economic Community Preparation - Mutiara Shifa (Proceedings of AICS - Social Sciences, 2017)
As a country facing global challenges, it will be said as ready when it experiences domestic growth measured through gross domestic product (GDP). Welcoming the ASEAN economic community 2017, necessarily the role of growth will show the readiness of community as a whole. In this study, the author will predict the calculation of GDP based on the influences of the bank financing growth. In banking, GDP is an indicator of economic growth which is an important measure in explaining direct economic performance and a performance of economic actors providing goods and services including the banking industry. Economic growth can increase the cash flow of banks by increasing demand for financing from companies and households. During periods of strong economic growth, financing demand tends to increase. Because the financing that tends to obtain better profits.